Treatment of Intrabony Defects with a Combination of Hyaluronic Acid and Deproteinized Porcine Bone Mineral - Darko Božić (MDPI AG, 2021)
Background: this study evaluates the clinical outcomes of a novel approach in treating deep intrabony defects utilizing papilla preservation techniques with a combination of hyaluronic acid (HA) and deproteinized porcine bone mineral. Methods: 23 patients with 27 intrabony defects were treated with a combination of HA and deproteinized porcine bone mineral. Clinical attachment level (CAL), pocket probing depth (PPD), gingival recession (REC) were recorded at baseline and 6 months after the surgery. Results: At 6 months, there was a significant CAL gain of 3.65 ± 1.67 mm (p < 0.001) with a PPD reduction of 4.54 ± 1.65 mm (p < 0.001), which was associated with an increase in gingival recession (0.89 ± 0.59 mm, p < 0.001). The percentage of pocket resolution based on a PPD ≤4 mm was 92.6% and the failure rate based on a PPD of 5 mm was 7.4%. Conclusions: the present findings indicate that applying a combined HA and xenograft approach in deep intrabony defects provides clinically relevant CAL gains and PPD reductions compared to baseline values and is a valid new approach in treating intrabony defects.